Neither MICA Nor DEPDC5 Genetic Polymorphisms Correlate with Hepatocellular Carcinoma Recurrence following Hepatectomy. (24th October 2012) - Motomura, Takashi; Ono, Yuki; Shirabe, Ken; Fukuhara, Takasuke; Konishi, Hideyuki; Mano, Yohei; Toshima, Takeo; Yoshiya, Shohei; Muto, Jun; Ikegami, Toru; Yoshizumi, Tomoharu; Maehara, Yoshihiko
Abstract : Purpose . Genetic polymorphisms of MICA and DEPDC5 have been reported to correlate with progression to hepatocellular carcinoma (HCC) in chronic hepatitis C patients. However, correlation of these genetic variants with HCC recurrence following hepatectomy has not yet been clarified. Methods . Ninety-six consecutive HCC patients who underwent hepatectomy, including 64 patients who were hepatitis C virus (HCV) positive, were genotyped for MICA (rs2596542) and DEPDC5 (rs1012068). Recurrence-free survival rates (RFS) were compared for each genotype. Results . Five-year HCC recurrence-free survival (RFS) rates following hepatectomy were 20.7% in MICA GG allele carriers, 38.7% in GA, and 20.8% in AA, respectively (P = 0.72 ). The five-year RFS rate was 23.8% in DEPDC5 TT allele carriers and 31.8% in TG/GG, respectively (P = 0.47 ). The survival rates in all (including HCV-negative) patients were also similar among each MICA and DEPDC5 genotype following hepatectomy. Among HCV-positive patients carrying the DEPDC5 TG/GG allele, low fibrosis stage (F0-2) occurred more often compared with TT carriers (P < 0.05 ). Conclusions . Neither MICA nor DEPDC5 genetic polymorphism correlates with HCC recurrence following hepatectomy. DEPDC5 minor genotype data suggest a high susceptibility for HCC development in livers, even those with low fibrosis stages.